الظواهر التركيبية في ديوان وعيناها لــ " محمد جربوعة" - كساب, مريقة, هناء فؤاد (Univercty of Eloued, 2020)
ترمي ىذه الدارسة إلى بركز الظكاىر التركيبية البلاغية في ديكاف كعيناىا لمحمد جربكعة ك الكقكؼ عمى أبرز الشكاىد الشعرية المتكاجدة في الديكاف مع استجلاء الصكرة الكناية ) ىذا كقد كانت مع/ـ قصائد الديكاف – الفنية البلاغية (الإستعارة - التشبيو تتحدث عف الغزؿ كعف المشاعر الجياشة كما ترقص بو دقات قمب الشاعر مف أحاسيس كعكاطؼ . كعمى ىذا الضكء إنتظـ البحث في فصميف تبعتيما مقدمة البحث كفصؿ تمييدم – النفي -التقديـ كالتأخير – أما الفصؿ الأكؿ فقد إحتكل عمى الظكاىر التركيبية (النداء الإستفياـ ) نظريا ,أما الفصؿ الثاني فخصص لدارسة الدي ك –القسـ اف حيث تضمف عمى جداكؿ تطبيقية لكؿ ظاىرة مف الظكاىر كبعض الصكر البلاغية الفنية كا نتيى البحث بخاتمة كانت حكصمة كنتيجة البحث This study aims at indicating the synthetic rhetorical phenomena in Mohammed DJARBOUA'A's divan ' oh Her Eyes wa ainaha ", pointing out the most prominent poetic quotations in the divan and elucidating their literary devices (simile, metaphor). Most of the divan's poems are about love, romance and passionate feelings, the emotions that the writer's heart carries.Accordingly, the work in hand is Divided into two chapters preceeded by a general introduction and a preliminary chapter. The first chapter tackles ،theoretically, the matter of the synthetic phenomena (call, negation, antecedence and postponement, Interrogation and oath). However, the second chapter is devoted to studying the divan, hence including applied information about each phenomena in addition to some of its rhetorical and literary devices. This work is sealed with a general conclusion that summarises this research and its results.
Keywords: النداء النفي الاستفهام اتقديم التأخير